Social appropriation of new technologies - Francisco Javier Moreno Gálvez; Francisco Sierra Caballero (Internet Policy Review, 2022)
The social appropriation of new technologies refers to technological and social processes of mediation in the interaction between social actors and technological devices. As such, the concept transcends relatively straightforward ideas of access and use of technology to focus on: how users develop technological and cognitive competences; the meaningful integration of the technological devices into subjects' everyday lives and behaviour; the active and creative production of meaning; social mediation within communities of users; and the way that the interests of communities of users are represented in public spaces. This text outlines the key concepts and debates in the appropriation of new technologies through a genealogical reconstruction of relevant academic traditions, including, amongst others, cultural studies and the sociology of the uses of new technologies. This interdisciplinary approach takes into account the technical, cognitive, educational and communicative dimensions of new technologies and how they may be useful for understanding contemporary processes of technological change.
Keywords: 300; Appropriation; Cultural production; Information capital